CITRA VISUAL MUSEUM HOUSE OF SAMPOERNA SEBAGAI IDENTITAS WISATA ARSITEKTUR - Kristiana, Nova (Visualita Jurnal Online Desain Komunikasi Visual, 2021)
ABSTRACT. The House of Sampoerna Museum does not only look how the history of cigarettes was made, but also the value of this historical place, such as the struggle to achieve success. Visiting the House Of Sampoerna Museum we will see art and cultural performances, live music, art galleries, unique cafes, shops selling various forms of handicrafts. The promotional strategy that has been carried out by managers of the House of Sampoerna is currently still not optimal and this has made the name of the House of Sampoerna limited to a cigarette museum. With the emergence of these problems, data were collected through field observations and interviews. Meanwhile, for the design of this study using 5W1H technical analysis in accordance with the needs of the problems studied to determine effective and communicative promotional media, namely merchandise in the form of key chains in the form of flip-flops with visuals from the House of Sampoerna Museum. Key word: promotion, tourism, architecture, House Of Sampoerna, museum